Selective COX-2 inhibitors and risk of thromboembolic events – regulatory aspects - Heim, Hans-Karl; Broich, Karl (Thrombosis and Haemostasis, 2006)
In the 1990s, the pharmaceutical industry developed selective COX-2 inhibitors (coxibs) as alternatives to conventional nonsteroidal anti-inflammatory drugs (NSAIDs), with the expectation of similar analgetic and anti-inflammatory efficacy but a reduced risk of adverse gastrointestinal (GI) effects. Marketing authorisation (MA) was granted for rofecoxib and celecoxib as first representatives of this new pharmacological class at the end of the 1990s in the EU. In the following years MAs were granted for the ´second generation` coxibs etoricoxib, parecoxib/valdecoxib and lumiracoxib. However, data from large clinical ´outcome studies` as well as epidemiological data raised concerns about the cardiovascular (CV) safety of the coxibs. In consequence, two comprehensive review processes (referrals) were initiated by the European Medicines Agency (EMEA).As a result, in the EU the use of coxibs has been contraindicated in patients with established coronary heart disease, cerebrovascular disease and peripheral arterial disease and a number of warning statements concerning CV, GI and skin toxicity have been introduced in the coxib product informations. This article provides a description of the regulatory actions taken and discusses some specific aspects of the past and future regulatory assessment of coxibs.
Keywords: Cyclooxygenase 2 inhibitors; anti-inflammatory agents; non-steroidal; cardiovascular diseases; gastrointestinal diseases; legislation; drug